Effect of Coated Silver Nanoparticles on Cancerous vs. Healthy Cells - Liubov Artiukh; Olga Povnitsa; Svitlana Zahorodnia; Calin V. Pop; Nodari Rizun (Journal of Toxicology)
Unique properties of silver nanoparticles (NPs) ensure their wide applications, in biomedicine; for this reason, it is very important carefully to study the toxicity of such NPs. The influence of silver nanoparticles coated with natural resin (Ag NPs) on the morphological and functional features of healthy BHK-21 and cancerous Hep-2 cells were studied using fluorescence microscopy, MTT, and neutral red assays. Ag NPs induced morphological changes in both cell cultures. The modifications were dose-dependent and more pronounced with an increase in NPs concentration. The IC50 value of Ag NPs for Hep-2 cells was found to be 2.19 ± 0.22 µg/mL, whereas for BHK-21 cells it was significantly (5x) higher at 10.92 ± 2.48 µg/mL. The use of NPs at a concentration close to IC50 leads to significant increase (up to 40%) in the number of necrotic cells in cancerous cell population and a decrease in the number of mitotic cells (up to 1.3%). In noncancerous cells the cellular parameters were similar to the control cells. These data suggest that the silver nanoparticles coated with natural resin can be potentially used in cancer therapy.